SUBSIDI BIBIT TANAMAN PADA DINAS PERTANIAN DAN KELAUTAN DI KOTA MEDAN SUMATERA UTARA TAHUN 2013-2015 - Hamsir Saputra; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The government of agriculture as a institution who give the some field at the worl, and some many things to atheror than a rice field. Many people in Medan City has a land to the agriculture and how to make the sand as a needly to our life. The simple our agriculture in this contrueiron, and how to the thaenme in the Medan City. As usully many things in other than our contry to add mire the agriculture.This research is to begin the government science to get the rice field and soon. Government of Agriculture has a program BLBU. In this research how to make the simple of agriculture of sand and land of the other in Medan City. As a student and research the simple of agriculture giving some reason to lay them publik of interst. The agriculture not giving to them. The agriculture is in Government at Amplas District in Medan City North Sumatera Province. As the result of this research is not giving to all them about BLBU.Key Word: Policy, The subsidi, and BLBU